G protein-coupled estrogen receptor (GPER) in adult boar testes, epididymis and spermatozoa during epididymal maturation - Krejčířová, Romana; Maňasová, Marie; Sommerová, Veronika; Langhamerová, Eva; Rajmon, Radko; Maňásková-Postlerová, Pavla (International journal of biological macromolecules, 2018)
The G protein-coupled estrogen receptor (GPER) is a transmembrane receptor considered as a mediator of rapid non-genomic responses. GPER has been found in the male reproductive tract of many mammalian species. However, in adult boars, GPER has been reported only in ejaculated spermatozoa. Therefore, we focused on GPER detection in testicular and epididymal tissues and sperm cells in adult boars. We found GPER in Leydig cells and seminiferous tubules of boar testes and in the secretory epithelium of epididymis. A weaker signal was visible in smooth muscle cells and spermatozoa in the epididymal tubule. In spermatozoa isolated from epididymal parts, GPER was found to localize mainly in the sperm acrosome and flagellum. We immunodetected several protein bands in the extracts of the tissues and epididymal spermatozoa. A significantly higher amount of GPER mRNA was detected in the spermatozoa from caput epididymis, whereas the mRNA expression was lower in tissues of testes and caput epididymal. Our results showed the first evidence of GPER in boar epididymal spermatozoa. Moreover, the GPER localization in adult boar testes, epididymis, and mature spermatozoa suggests the involvement of estrogens via transmembrane receptor and rapid non-genomic signaling in both the sperm development and post-testicular maturation.
Keywords: Epididymal spermatozoa; messenger RNA; epididymis; Epididymis; Receptors, G-Protein-Coupled; Sperm Maturation; mužské pohlaví; testis; Swine; Adult boar testes; receptory spřažené s G-proteiny; RNA, Messenger; zvířata; zrání spermie; prasata; Spermatozoa; GPER; Testis; spermie; Male; Animals